PENAFSIRAN AL-DAKHÎL DALAM AL-JÂMI’ LI AHKÂM AL-QUR`AN KARYA AL-QURTUBÎ (Analisis Penafsiran Surat Yusuf) - Yasser Muda Lubis (LP2M Universitas PTIQ Jakarta, 2021)
One of the books of interpretation that is often used as a reference in the study of interpretation is the book of interpretation by al-Qurtubî. This book of interpretation is included in the category of al-Tafsîr al-Ma`tsȗr. In its interpretive methodology, al-Qurtubî requires relying on a history to its narrators, and refrains from mentioning stories that are widely quoted by commentators and news from historians. However, it turns out that al-Qurtubî (read: al-Qurtubî methodology) does not fully implement the methodology specified in its interpretation. This paper shows the interpretation of al-Dakhîl in the book of interpretation of al-Jâmi' li Ahkâm al-Qur`an which includes the use of fake status history, weak status history, mast 'anhu isrâîliyyât history, and the use of isrâîliyyât history that contradicts the texts. Al-Qur'an, Hadith of the Prophet Muhammad. and common sense (mukhâlif). The findings of this paper were obtained after examining the narrations and their contents, analyzing the contents of the commentary book of al-Jâmi' li Ahkâm al-Qur`an, especially in Surah Yusuf, then proceeding to compare it with other commentary books that deserve to be used as a guide. This paper is expected to contribute to the alignment of the interpretation of the Qur'an from the various elements of al-Dakhîl contained in this book of interpretation of the Qur'an and is also expected to enrich the scientific treasures relating to the theme of al-Dakhîl in interpretation